A transição da Educação Infantil para o Ensino Fundamental: uma revisão de literatura - Tavares Gasparone, Nathalia (2023)
The article intends to analyze the results from researches about student’s transition from kindergarten schools to elementary schools, through researching revised pieces published at CAPES (Coordination for the Improvement of Higher Education Personnel), from the year 2017 to 2022. Upon reading the selected articles, it's possible to conclude that a great number of schools’ managers and teachers are aware of the importance of welcoming kids with kindness and respect to this particular moment of student's l ife, but it’s not what really happens on a regular basis, which can cause insecurity and anxiety in students